Dmitriy Mandzhiev, My Family Relics: The Diamond Sutra - Terbish, Baasanjav (Kalmyk Cultural Heritage Documentation Project, University of Cambridge, 2018)
Dmitriy talks about his family relic, the Diamond Sutra, that his family inherited from their grandmother: We have at home an old sutra of Dorzh Zhodva (i.e. Diamond Sutra). It belonged to our grandmother. She took it with her to Siberia. Our grandmother, as far as I remember, received this sutra from her maternal uncle. She never let us to touch it, or to be near it. When she lit a candle, we would come to her to receive blessings from the sutra. Rarely, she invited a monk to have her sutra ‘aired’ (sal’k orulkh). The monk unwrapped its cover and turned the pages. Today we retain this tradition and invite lamas from time to time to have the sutra ‘aired’. Under no circumstance can anyone touch it with dirty hands. Ideally before touching it, one has to have a shower.
Keywords: Sutra; family relic